2021
DOI: 10.3389/fnagi.2020.615852
|View full text |Cite
|
Sign up to set email alerts
|

Deviations in Hippocampal Subregion in Older Adults With Cognitive Frailty

Abstract: BackgroundCognitive frailty is a particular state of cognitive vulnerability toward dementia with neuropathological hallmarks. The hippocampus is a complex, heterogeneous structure closely relates to the cognitive impairment in elderly which is composed of 12 subregions. Atrophy of these subregions has been implicated in a variety of neurodegenerative diseases. The aim of this study was to explore the changes in hippocampal subregions in older adults with cognitive frailty and the relationship between subregio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Such subregions are associated with functions such as cognitive processing (information input and output capacity), visuospatial function, memory, fear regulation (situational learning and emotional memory) and hippocampal circuitry function and cognitive behavior. Thus, this more severe atrophy in the brain parenchyma and a reduction in the total number of white matter fibers in the group of older adults with cognitive frailty may indicate the pathway of association between low short-term memory, depressive symptoms and lower physical abilities 59 .…”
Section: Discussionmentioning
confidence: 96%
“…Such subregions are associated with functions such as cognitive processing (information input and output capacity), visuospatial function, memory, fear regulation (situational learning and emotional memory) and hippocampal circuitry function and cognitive behavior. Thus, this more severe atrophy in the brain parenchyma and a reduction in the total number of white matter fibers in the group of older adults with cognitive frailty may indicate the pathway of association between low short-term memory, depressive symptoms and lower physical abilities 59 .…”
Section: Discussionmentioning
confidence: 96%
“…Although previous studies have indicated that white matter hyperintensity lesions are associated with CF, this is the first report of a population-based study. In addition, we analyzed SVD in more detail than in previous studies 13 15 , including evaluations of lacunar infarcts and microbleeds. We also examined MTL region volumes because volume reductions have been linked to early pathological changes in Alzheimer’s disease, the most frequent dementia to develop from amnestic MCI.…”
Section: Discussionmentioning
confidence: 99%
“…Four recent studies have investigated brain structural changes associated with CF using magnetic resonance imaging (MRI) 12 15 . These studies reported that compared to healthy adults without CF, those with CF had increased white matter hyperintensity lesions 12 , 13 and greater volume reductions (atrophy) in the bilateral thalamus, left caudate, right pallidum, right accumbens 14 , and bilateral hippocampal subregions 15 . These lesion and atrophy patterns suggest that CF is a sign of progressive vascular pathology and neurodegenerative processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the progression of AD, specific anatomical areas of the hippocampus tend to atrophy [ 17 ]. In older adults with cognitive frailty, a significant volume decrease occurs in the bilateral presubiculum, the left parasubiculum, the hippocampal amygdala transition area (HATA), and the CA1 area [ 18 ], while compared to the MCI, the volume of the right molecular layer/right CA4 is significantly smaller and correlated with the cognitive performance (measured with MMSE) in AD [ 19 , 20 ]. Although the above research showed difference alteration in the hippocampal subregions in the progression of AD, a comprehensive study on the structural characteristics of the hippocampal subregion networks which are affected by hypertension in SCD is lacking.…”
Section: Introductionmentioning
confidence: 99%